Inter-clonal Variation in Carbon Pool of Populus Deltoides Bartr - Pal, Rama; Melkania, Uma; Dhiman, R. C. (Indian Forester, 2009)
Climate change and forests are intrinsically linked. On the one hand, changes in global climate are already stressing forests through higher mean annual temperatures, altered precipitation patterns and more frequent and extreme weather events. At the same time, forests and the wood they produce, trap and store CO2, play a major role in mitigating climate change. During the course of this study, potential of carbon sequestration, one of the major intangible benefits, was studied for 14 Populus deltoides clones. The carbon content was determined in different parts of trees i.e., bole, bark and branches. The results showed that the carbon content was found in the order: bole>branches>bark. Clone ’WIMCO-22’ was found the best in terms of carbon stock while WIMCO-42’ was the poorest one in this respect.